Proposed Modified Directed RRT Algorithm of the Basic RRT (Al-Mansour Journal, 2022)
Abstract: Due to the development of intelligent systems and the increasing use of path planning algorithms, problems in motion planning appear and finding algorithms to solve such issues efficiently have become the new challenges for researchers. This paper presents Directed (Rapidly Exploration Randomly Tree) algorithm as a modification of the traditional RRT searching algorithm. The fundamental idea is to enhance and utilize RRT algorithm in term of solving path planning problems. This work accomplished by taking the searching directions of the basic RRT algorithm into consideration. The experiment result of the enhanced algorithm simulation shows promising result and encourage researcher to search further in this field.
Keywords: Artificial intelligent; Motion planning; Robot; RRT Algorithm.